Analysis of the Duodenal Microbiome in Autistic Individuals: Association With Carbohydrate Digestion - Kushak, Rafail I; Winter, Harland S; Buie, Timothy M; Cox, Stephen B; Phillips, Caleb D; Ward, Naomi L (Journal of pediatric gastroenterology and nutrition, 2017)
There is evidence that symptoms of maldigestion or malabsorption in autistic individuals are related to changes in the indigenous microbiota. Analysis of colonic bacteria has revealed microbial dysbiosis in children with autism; however, characteristics of the duodenal microbiome are not well described. In the present study the microbiome of the duodenal mucosa of subjects with autism was evaluated for dysbiosis, bacteria overgrowth, and microbiota associated with carbohydrate digestion. The relationship between the duodenal microbiome and disaccharidase activity was analyzed in biopsies from 21 autistic subjects and 19 children without autism. Microbiota composition was determined by 16S ribosomal RNA gene sequencing, and disaccharidase activity via biochemical assays. Although subjects with autism had a higher frequency of constipation (P < 0.005), there was no difference in disaccharidase activity between groups. In addition, no differences in microbiome diversity (species richness and evenness) were observed. Bacteria belonging to the genus Burkholderia were more abundant in subjects with autism, whereas members of the genus Neisseria were less abundant. At the species level, a relative decrease in abundance of 2 Bacteroides species and Escherichia coli was found in autistic individuals. There was a positive correlation between the abundance of Clostridium species, and disaccharidase activity, in autistic individuals. There are a variety of changes at the genus and species level in duodenal microbiota in children with autism that could be influenced by carbohydrate malabsorption. These observations could be affected by variations in individual diets, but also may represent a more pervasive dysbiosis that results in metabolites that affect the behavior of autistic children.